Nahdlatul Ulama, Abdurrahman Wahid and Reformation: What Does NU's November 1997 National Gathering Tell Us? - Greg Barton; Andrée Feillard (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1999)
A year in politics almost anywhere is a long time, in Indonesia the twelve month period from November 1997 to November 1998 was a very long time. Not since the mid 1960s had so much taken place in one year. For Nahdlatul Ulama (NU), Indonesia's thirty to forty million strong traditionalist Islamic organization, as for almost every other organization in Indonesia, the year was an extraordinary one.DOI: 10.15408/sdi.v6i1.745